Образ українців у подорожньому щоденнику Павла Халебського (Алеппського) «Опис подорожі патріарха Макарія» - Випасняк, Г. (Народознавчі зошити, 2013)
Статтю присвячено дослідженню образу українців у подорожньому щоденнику Павла Халебського, сина Антіохійського патріарха Макарія Третього. У центрі уваги — релігійне життя українців, змалювання храмів, монастирів,
побуту ченців тощо. Особливо виділяються постать Богдана Хмельницького і колективний образ козаків як зразки
духовного лицарства. The article has brought some results of studies in the image of
Ukrainians noted by Paul of Aleppo, son of Makarios III, Patriarch
of Antioch, in his journey diary. His especial attention
deacon Paul had paid to Ukrainians’ religious life as well as to
descriptions of temples and monasteries, monastic life etc.
Figure of Bohdan Khmelnytsky and collective representation of
Cossackdom have been thoroughly exposed as true specimens
of spiritual knighthood and nobility. Статья посвящена исследованию образа украинцев в дорожном дневнике Павла Алеппского, сына патриарха Антиохийского Макария Третьего. В центре внимания — прежде всего религиозная жизнь украинцев, описание
храмов, монастырей, быта монахов и т. п. Особое значение
придается фигуре Богдана Хмельницкого и коллективному образу казачества как образцам духовного рыцарства.